Effect of Taro (Colocasia esculenta) Starch-Hydrocolloids Mixture on the Physical and Sensory Characteristics of Leavened Bread - Feroz Alam,; Anjum Nawab,; Tanveer Abbas,; Mohib Kazimi ,; Abid Hasnain, (Journal of Pharmacy and Nutrition Sciences, 2015)
During this study, different blends of taro starch-hydrocolloid were incorporated in yeast leavened bread and their effects were investigated. The specific volume, moisture content and slice shape of the bread were found to be improved by the addition of taro starch-guar gum blend. Taro starch-xanthan gum mixture was also found to be a good additive to improve specific volume, slice shape, crumb softness as well as sensory characteristics of bread. The study reveals taro starch-hydrocolloid blend can be utilized as a novel ingredient to improve the physical and sensory characteristics of leavened bread.